Easy Limit

Calculus Level 3

lim x ( x 3 + 3 x 2 3 x 2 2 x ) = ? \large \displaystyle\lim_{x\to\infty} \left( \sqrt[3]{x^3+3x^2}-\sqrt{x^2-2x} \right) = \ ?


The answer is 2.0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Prakhar Bindal
Mar 5, 2017

Well this problem becomes very easy if we use (1+x)^ n = 1+nx with x approaches zero

Take x^3 and x^2 common respectively from the two radicals and use above identity to get

x(1+1/x)-x(1-1/x) = 2

bhai, wo ek activation energy ka numerical aata hai board me , uska ek tarika hota hai thuje pta hai kya yaar? waise toh ppr me nikalne ni wala log or calculations bhut hoti hai usme :{

A Former Brilliant Member - 4 years, 3 months ago

Log in to reply

Arrhenius equation mein log le le . fir compare kar le Frequency factor aur Activation energy is value aa jaaegi

Prakhar Bindal - 4 years, 3 months ago

Log in to reply

nhi bhai wo bhut bdi calculations aati hai phir anti log lena pedta h uski ek trick bi hoti h. mai ek Q dikhata hu thuje thik ?

A Former Brilliant Member - 4 years, 3 months ago

bhai hogi tyari ?

A Former Brilliant Member - 4 years, 3 months ago

First I am going to expand this expression to lose the square root, doing that by using the identity ( a b ) ( a + b ) = a 2 b 2 (a-b)(a+b)=a^2-b^2 :

lim x ( x 3 + 3 x 2 3 x 2 2 x ) = lim x ( { x 3 + 3 x 2 3 x 2 2 x } x 3 + 3 x 2 3 + x 2 2 x x 3 + 3 x 2 3 + x 2 2 x ) \displaystyle\lim_{x\to\infty} \left( \sqrt[3]{x^3+3x^2}-\sqrt{x^2-2x} \right) =\displaystyle\lim_{x\to\infty} \left( \{\sqrt[3]{x^3+3x^2}-\sqrt{x^2-2x}\}\color{#3D99F6}{\frac{\sqrt[3]{x^3+3x^2}+\sqrt{x^2-2x}}{ \sqrt[3]{x^3+3x^2}+\sqrt{x^2-2x}}} \right)

After multiplying, we get the following expression:

lim x ( ( x 3 + 3 x 2 ) 2 3 x 2 2 x x 3 + 3 x 2 3 + x 2 2 x ) \displaystyle\lim_{x\to\infty} \left(\frac{\sqrt[3]{(x^3+3x^2)^2}-x^2-2x}{ \sqrt[3]{x^3+3x^2}+\sqrt{x^2-2x}} \right)

Now I am going to expand again, this time to lose the 3rd root, doing that by using the identity ( a b ) ( a 2 + a b + b 2 ) = a 3 b 3 (a-b)(a^2+ab+b^2)=a^3-b^3 :

lim x ( ( x 3 + 3 x 2 ) 2 3 x 2 2 x x 3 + 3 x 2 3 + x 2 2 x ( x 3 + 3 x 2 ) 4 3 + ( x 2 2 x ) ( x 3 + 3 x 2 ) 2 3 + ( x 2 2 x ) 2 ( x 3 + 3 x 2 ) 4 3 + ( x 2 2 x ) ( x 3 + 3 x 2 ) 2 3 + ( x 2 2 x ) 2 ) \displaystyle\lim_{x\to\infty} \left( \frac{\sqrt[3]{(x^3+3x^2)^2}-x^2-2x}{ \sqrt[3]{x^3+3x^2}+\sqrt{x^2-2x}}\color{#3D99F6}{\frac{\sqrt[3]{(x^3+3x^2)^4}+(x^2-2x)\sqrt[3]{(x^3+3x^2)^2}+(x^2-2x)^2}{\sqrt[3]{(x^3+3x^2)^4}+(x^2-2x)\sqrt[3]{(x^3+3x^2)^2}+(x^2-2x)^2} }\right)

After expanding we get:

lim x ( ( x 3 + 3 x 2 ) 2 ( x 2 2 x ) 3 ( ( x 3 + 3 x 2 ) 4 3 + ( x 2 2 x ) ( x 3 + 3 x 2 ) 2 3 + ( x 2 2 x ) 2 ) ( x 3 + 3 x 2 3 + x 2 2 x ) ) \displaystyle\lim_{x\to\infty} \left(\frac{(x^3+3x^2)^2-(x^2-2x)^3}{(\sqrt[3]{(x^3+3x^2)^4}+(x^2-2x)\sqrt[3]{(x^3+3x^2)^2}+(x^2-2x)^2)( \sqrt[3]{x^3+3x^2}+\sqrt{x^2-2x})} \right)

Now by expanding the numerator of this fraction, and dividing (and multiplying) the denominator with x 5 x^5 , we get

lim x ( 12 x 5 3 x 4 + 8 x 3 x 5 ( ( 1 + 3 x ) 4 3 + ( 1 2 x ) ( 1 + 3 x ) 2 3 + ( 1 2 x ) 2 ) ( 1 + 3 x 3 + 1 2 x ) ) \displaystyle\lim_{x\to\infty} \left(\frac{12x^5-3x^4+8x^3}{\color{#3D99F6}{x^5}(\sqrt[3]{(1+\frac{3}{x})^4}+(1-\frac{2}{x})\sqrt[3]{(1+\frac{3}{x})^2}+(1-\frac{2}{x})^2)( \sqrt[3]{1+\frac{3}{x}}+\sqrt{1-\frac{2}{x}})} \right)

Now by dividing(and multiplying) the nominator with x 5 x^5 we get:

lim x ( x 5 ( 12 3 x + 8 x 2 ) x 5 ( ( 1 + 3 x ) 4 3 + ( 1 2 x ) ( 1 + 3 x ) 2 3 + ( 1 2 x ) 2 ) ( 1 + 3 x 3 + 1 2 x ) ) \displaystyle\lim_{x\to\infty} \left(\frac{\color{#D61F06}{x^5}(12-\frac{3}{x}+\frac{8}{x^2})}{\color{#D61F06}{x^5}(\sqrt[3]{(1+\frac{3}{x})^4}+(1-\frac{2}{x})\sqrt[3]{(1+\frac{3}{x})^2}+(1-\frac{2}{x})^2)( \sqrt[3]{1+\frac{3}{x}}+\sqrt{1-\frac{2}{x}})} \right)

And finally, by using the limits lim x 1 x = 0 \lim_{x\to\infty} { \frac{1}{x}}=0 and lim x 1 x 2 = 0 \lim_{x\to\infty}\frac{1}{x^2}=0 we get:

lim x ( ( 12 3 x + 8 x 2 ) ( ( 1 + 3 x ) 4 3 + ( 1 2 x ) ( 1 + 3 x ) 2 3 + ( 1 2 x ) 2 ) ( 1 + 3 x 3 + 1 2 x ) ) = 12 ( 1 + 1 + 1 ) ( 1 + 1 ) = 12 6 \displaystyle\lim_{x\to\infty} \left(\frac{(12-\frac{3}{x}+\frac{8}{x^2})}{(\sqrt[3]{(1+\frac{3}{x})^4}+(1-\frac{2}{x})\sqrt[3]{(1+\frac{3}{x})^2}+(1-\frac{2}{x})^2)( \sqrt[3]{1+\frac{3}{x}}+\sqrt{1-\frac{2}{x}})} \right)=\frac{12}{(1+1+1)(1+1)}=\frac{12}{6}

lim x ( x 3 + 3 x 2 3 x 2 2 x ) = 2 \boxed{ \displaystyle\lim_{x\to\infty} \left( \sqrt[3]{x^3+3x^2}-\sqrt{x^2-2x} \right) = 2}

Faster approach: Use y = 1/x and binomial approximation: (1+x)^n approx 1 + nx

Pi Han Goh - 5 years, 7 months ago

Log in to reply

It can be done without the substitution: lim x ( x 3 + 3 x 2 \leftroot 2 \uproot 23 x 2 2 x \leftroot 2 \uproot 2 ) = lim x ( x 1 + 3 x \leftroot 2 \uproot 23 x 1 2 x \leftroot 2 \uproot 2 ) = lim x ( x ( 1 + 1 x ) x ( 1 1 x ) ) = 2 \lim_{x\to\infty} \left( \sqrt[\leftroot{-2}\uproot{2}3]{x^3+3x^2}-\sqrt[\leftroot{-2}\uproot{2}]{x^2-2x} \right) =\lim_{x\to\infty} \left( x\sqrt[\leftroot{-2}\uproot{2}3]{1+\frac{3}{x}}-x\sqrt[\leftroot{-2}\uproot{2}]{1-\frac{2}{x}} \right)=\lim_{x\to\infty} \left( x(1+\frac{1}{x})-x(1-\frac{1}{x}) \right)=2

Miloje Đukanović - 5 years, 7 months ago

Log in to reply

Did the same

saptarshi dasgupta - 5 years, 3 months ago

u r making it excessively tedious :|

A Former Brilliant Member - 4 years, 3 months ago
Carlos Victor
Nov 8, 2015

Use y=1/x and L´HOSPITAL rule.

How?Can you elaborate your answer?

Anik Mandal - 5 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...